Calibration And Validation Of Vissim Simulation A Case Study Of Priority Bus Lane - Chong, Jia Wei (Universiti Sains Malaysia, 2021)
Urban sprawl, rapid growth in population and increasing usage of cars have caused higher traffic volumes, leading to traffic congestion which has worsened air pollution and the greenhouse gas emissions. Penang has experienced traffic congestion on many main roads especially in the central business district (CBD) during weekday peak hours. As a result, delays and travel times of public transport have increased which has discouraged the public to use the public transport. This study aims to examine the traffic volume at the selected bus stop area. The traffic characteristics will be simulated using VISSIM. In this study, data collection was conducted through video recording for traffic counting and spot speed study to obtain the number and speed distribution of the vehicle. The data collected was input into VISSIM microscopic simulation software for further simulation. Then, verification, calibration and validation were performed to observe the ability of VISSIM simulation software to represent the traffic characteristics portrayed in the recorded video. The calibrated model was used to simulate and evaluate the efficiency of the introduction of priority bus lane to the original road network. The results of verification show that the simulated average speed of the vehicle accurately represents the speed of one vehicle as identified from the spot speed study. The results of calibration of the simulated model showed minimum deviation of the simulated model from the real scenario portrayed in the provided video. The simulation results prove that the introduction of priority bus lane is not effective for this case study. Therefore, the future study should consider the frequency of the bus arrival on the particular bus stop as a more determinant factor influencing the traffic condition. The findings in this study will be used as a reference for state government to implement public transport policy in reducing state traffic congestion.